2013
DOI: 10.1080/10503307.2012.721937
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and intensity of day hospital treatment for eating disorders

Abstract: The purpose of the study was to compare the effectiveness of 4-day versus 5-day day hospital (DH) treatment and to document effectiveness based on a large sample size. Participants were 801 patients, diagnosed with an eating disorder, who participated in DH treatment from 1985 to 2009. The study followed a sequential cohort ABA design. Higher intensity DH was associated with higher rates of abstinence from bingeing and vomiting and larger improvements in depression and body dissatisfaction. Higher intensity DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
1
38
0
1
Order By: Relevance
“…The DH is both intensive and highly contained. The typical trajectory for most patients is a quick and dramatic symptom reduction (McFarlane, MacDonald, Trottier, & Olmsted, in press;Olmsted et al, 2013), though of course not all remit. As such, it makes sense that the threshold to define those who are truly doing well is a stringent criterion, which would require a different degree of improvement than that necessitated by outpatient individual therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The DH is both intensive and highly contained. The typical trajectory for most patients is a quick and dramatic symptom reduction (McFarlane, MacDonald, Trottier, & Olmsted, in press;Olmsted et al, 2013), though of course not all remit. As such, it makes sense that the threshold to define those who are truly doing well is a stringent criterion, which would require a different degree of improvement than that necessitated by outpatient individual therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Day hospital (DH) programs for BN are far more intensive than individual CBT and typically provide 35e40 h per week of hospitalbased treatment (e.g., Olmsted, McFarlane, Trottier, & Rockert, 2013). Therefore DH treatment is shorter in duration but more intensive, and includes a much higher degree of behavioral containment.…”
Section: Empirical Definitions Of Rapid Responsementioning
confidence: 99%
“…All patients attended all psychological therapy groups including: assertiveness training, family relationships group, interpersonal therapy group, art therapy group, and body image group, among others. This program was developed based on the Toronto Hospital day treatment program for eating disorders (Olmsted, McFarlane, Molleken, & Kaplan, 2001) and shares components common to such programs (Zipfel et al, 2002). Staff members had at least five years of experience in eating disorder treatment or day hospital programs.…”
Section: Methodsmentioning
confidence: 99%
“…One study found that eating disorder symptoms at discharge were predicted by eating disorder symptoms on admission, level of patients' confidence to change, patients' social quality of life and level of carers' expressed emotion among 107 participants with AN [2], However the study utilized a mixed sample initially comprised of 161 adolescent and adult Inpatients and 16 adult DTP patients from a range of treatment centres and did not specify how many (if any) DTP patients were included in the regression analysis which identified these predictors of outcome [2], Other studies found ( and body dissatisfaction, a higher intensity DTP produced better outcomes (Olmsted et al, 2013) though four-day DTPs can result in large effect sizes for symptom reduction (Crino and Djokvucic, 2010;Kong, 2005;Olmsted et al, 2013) and decrease in depression (Kong, 2005). In relation to achieving weight restoration, the assertion that there may be a "critical threshold" (Olmsted et al, 2013, p. 8) of therapeutic support necessary appears to be supported by the results from DTPs of varying intensities, indicating that underweight patients are generally able to increase their weight significantly during admission to day treatment, and with large effect sizes.…”
Section: Symptom-frequency Change Among Participants With Binge/vomitmentioning
confidence: 99%